Direct 3D-printing of cell-laden constructs in microfluidic architectures. Issue 8 (16th March 2016) - Liu, Justin; Hwang, Henry H.; Wang, Pengrui; Whang, Grace; Chen, Shaochen
Abstract : We demonstrate an optical 3D-printing method to build a microfluidic micromixer with the ability to directly print cell-laden scaffolds within. Abstract : Microfluidic platforms have greatly benefited the biological and medical fields, however standard practices require a high cost of entry in terms of time and energy. The utilization of three-dimensional (3D) printing technologies has greatly enhanced the ability to iterate and build functional devices with unique functions. However, their inability to fabricate within microfluidic devices greatly increases the cost of producing several different devices to examine different scientific questions. In this work, a variable height micromixer (VHM) is fabricated using projection 3D-printing combined with soft lithography. Theoretical and flow experiments demonstrate that altering the local z -heights of VHM improved mixing at lower flow rates than simple geometries. Mixing of two fluids occurs as low as 320 μL min −1 in VHM whereas the planar zigzag region requires a flow rate of 2.4 mL min −1 before full mixing occurred. Following device printing, to further demonstrate the ability of this projection-based method, complex, user-defined cell-laden scaffolds are directly printed inside the VHM. The utilization of this unique ability to produce 3D tissue models within a microfluidic system could offer a unique platform for medical diagnostics and disease modeling.